Análise espaço-temporal da Leishmaniose tegumentar americana em um circuito espacial de produção na Amazônia Oriental - NUNES, Mayara Mariana Costa (Universidade Federal do Pará, 2023)
The Northeast and Southeast regions of Pará concentrate a high incidence of cases of American cutaneous leishmaniasis (ACL). It is a disease characterized as one of the main neglected tropical diseases and constitutes a challenge for public health, requiring a great operational, technical and political effort, given the environmental nature involved in the epidemiology of the disease. In this scenario, understanding the secular behavior of the disease, considering regional peculiarities, can be of great value for planning future actions. This study aimed to analyze the spatio-temporal distribution of ATL in 12 municipalities that are part of a disease production circuit in the Southeast and Northeast mesoregions of the state of Pará. For this purpose, a descriptive study of the ecological type, of a quantitative nature, was carried out through a retrospective investigation of clinical, spatial and epidemiological data from ACL, based on data collected from the Notifiable Diseases Information System in 2006. to 2020. In total, 5,097 cases of the disease were reported during the study period. The incidence fluctuated over the period analyzed, ranging from 0.64/10,000 inhabitants in 2006 to 11.5/10,000 inhabitants in 2007, showing a stationary trend. Sociodemographic data revealed that the disease primarily affects men (83.6%) in their most productive phase (75.7%) and that the disease is related to fieldwork activities (62.7%). Most cases were autochthonous, but cases were reported from two countries in Latin America and two in Africa. The highest incidences were observed in the southeast of Pará and in the municipalities of the northeast of Pará that border Paragominas. The distribution of cases may be related to mining activities that led to deforestation and population migrations from other municipalities and states, especially the state of Maranhão, in search of jobs, generating a population jump. The importance of understanding the ATL transmission process at the local level is a fundamental issue to support surveillance and environmental control actions, and to contribute to the knowledge of the dynamics and circulation of the parasite between the foci of the same high transmission region.